﻿Magnetic properties of Sr1.5La0.5FeMoO6-δ depending on the phase composition of the reaction mixture - Marta V. Yarmolich; Nikolay A. Kalanda; Alexander V. Petrov; Dmitry A. Kiselev; Nikolay A. Bosak (Modern Electronic Materials, 2023)
This paper presents investigations of phase transformations during the crystallization of Sr1.5La0.5FeMoO6-δ by the solid-phase technique from a stoichiometric mixture of oxides MoO3, La2O3 and Fe2O3 and SrCO3 and precursors Sr0.5La0.5FeO3 and SrMoO4. Using XRD and thermogravimetric analyses, the influence of synthesis modes on the chemical processes occurring during the formation of double perovskite was studied. It has been established that the synthesis of lanthanum-strontium ferromolybdate in a mixture of oxides proceeds through a number of series-parallel stages. At the initial stage of interaction, the resulting lanthanum-strontium ferromolybdate is enriched with iron and its composition changes during the reaction towards an increase in the molybdenum content. As the temperature increases, the content of double perovskite increases, and the concentration of the secondary phase SrMoO4 does not disappear to zero until the synthesis temperature, which indicates that solid-phase reactions with the formation of a solid solution Sr1.5La0.5FeMoO6-δ from oxides are difficult to occur. It was determined that to minimize the influence of intermediate reaction products it is necessary to use precursors Sr0.5La0.5FeO3 and SrMoO4. Based on the results of studying the temperature dependences of the degree of phase transformations during the crystallization of double perovskite, combined heating modes were optimized. The use of optimized synthesis modes made it possible to obtain single-phase Sr1.5La0.5FeMoO6-δ powder with the superstructural ordering (82%), the Curie temperature of 450 K and a magnetization value of 40.9 A · m2 · kg-1 at T = 77 K in a magnetic field with induction B ≥ 0.86 T.